KUALITAS PELAYANAN DAN PENGGUNAAN APLIKASI SI-APIK TERHADAP PENERIMAAN PAJAK DENGAN KEPATUHAN PAJAK SEBAGAI VARIABEL INTERVENING - Triono, Bangkit; Ayem, Sri; Erawati, Teguh (Universitas Muhammadiyah Palembang, 2022)
This study was conducted to determine whether the quality of service and the use of the Si-apik application have an effect on tax compliance, and whether there is an effect of tax compliance on tax revenue, and to determine whether the quality of tax services and the use of the Si-apik application affect tax revenue in the city of Yogyakarta. The data used is primary data obtained randomly by distributing questionnaires, with details of the number of questionnaires distributed as many as 110, 106 returned questionnaires, and 100 questionnaires that can be processed and the rest are defective. The data analysis technique was carried out with the t test, R2 test, and path analysis. It was concluded that the quality of service and the use of si-apik applications had an effect on tax compliance. The service quality variable has an effect on tax revenue, while the use of the Si-apik application has no effect on tax revenue. The variable of taxpayer compliance has an effect on tax revenue in the city of Yogyakarta.